1987
DOI: 10.3109/00016488709134697
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Function in Hereditary Motor and Sensory Neuropathy (Charcot-Marie-Tooth Disease)

Abstract: Fourteen patients with hereditary motor and sensory neuropathy (HMSN), 12 of Type I and 2 of Type II, were assessed for auditory dysfunction. Five patients complained of hearing loss and all had pure-tone audiograms outside the normal range, while one patient who did not complain of hearing impairment also had an abnormal pure-tone audiogram. Assessment of loudness function, speech audiometry and brainstem auditory evoked potentials (BAEP) suggested that the hearing loss was the result of VIII nerve dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…[4][5][6] Kovach et al 1 found altered BAEP and otoacoustic emissions results in the study family, which were similar to those in our case, suggesting that there are audiological differences between families with CMT disease and dysacusis. The mechanism of cochlear involvement, however, remains unclear.…”
Section: Musiek Et Alsupporting
confidence: 72%
See 1 more Smart Citation
“…[4][5][6] Kovach et al 1 found altered BAEP and otoacoustic emissions results in the study family, which were similar to those in our case, suggesting that there are audiological differences between families with CMT disease and dysacusis. The mechanism of cochlear involvement, however, remains unclear.…”
Section: Musiek Et Alsupporting
confidence: 72%
“…Starr et al 6 reported 8 subjects with CMT disease that presented absent BAEP and normal otoacoustic emissions, which were characterized as auditory neuropathy. 5 As our case had altered otoacoustic emissions, the diagnosis of auditory neuropathy did not apply; however, BAEP and otoacoustic emissions changes were probably due to demyelinated auditory pathways because of CMT disease.…”
Section: Musiek Et Almentioning
confidence: 99%
“…Whilst the peripheral portion of the auditory nerve is the most likely site of lesion associated with the auditory symptoms [48], studies in Slovene, Italian and Bulgarian gypsy families have suggested a mutation in the chromosome 8 (genetic locus 8q24.3) inherited in an autosomal recessive pattern as the genetic basis of the associated AN/AD phenotype [49][50][51][52]. In addition, AN/AD also occurs in the most common form of the disease, the mutation in the genetic locus 17p11.2, inherited in an autosomal dominant fashion [53,54]. Histopathologic evidence indicates cochlear hair cell survival, despite the loss of spiral ganglion cells, and demyelinating processes in the VIIIth nerve in these patients [55].…”
Section: Pathology-pathophysiologymentioning
confidence: 98%
“…Hearing loss and deafness is an uncommon phenotypic variant in Charcot-Marie-Tooth (CMT) (Satya-Murti et al, 1980;Raglan et al, 1987). Recent studies have focused attention on auditory function in CMT by identifying hearing disorder as a prominent feature in several distinct genetic variants including primary demyelinating forms (CMT1) due to mutation of PMP22 gene duplication (Boerkoel et al, 2002;Kovach et al, 2002;Hattori et al, 2003;Joo et al, 2004), primary axonal forms (CMT2) due to mutations of MPZ gene (Chapon et al, 1999;De Jonghe et al, 1999;Misu et al, 2000;Hattori et al, 2003;Starr et al, 2003), connexin 31 (GJB3) gene (Lopez-Bigas et al, 2001), Connexin 32 (Cx32) gene (Boerkoel et al, 2002;Hattori et al, 2003), and in a mixed demyelinating/axonal autosomal recessive motor-sensory neuropathy, HMSN-Lom, particular to Roma populations due to a mutation of the NDRG1 gene (Kalaydjieva et al, 1998;Butinar et al, 1999;Kalaydjieva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that subclinical forms of auditory neuropathy might also be present in other hereditary neuropathies. For instance, abnormalities of auditory brainstem responses without subjective complaints of hearing problems have been described in individuals with Friedreich's ataxia (SatyaMurti et al, 1980), multiple sclerosis (Starr and Achor, 1975;Furst et al, 2000), and various degenerative disorders (Cassandro et al, 1986;Raglan et al, 1987). Asymptomatic vestibular nerve dysfunction can also occur in subjects with auditory neuropathy (Fujikawa and Starr, 2000).…”
Section: Introductionmentioning
confidence: 99%